Association between Obesity, Race and Knee Osteoarthritis: The Multicenter Osteoarthritis Study - He, Xin; Lu, Xiaoxiao; Chen, Shuo; Hochberg, Marc C.; Lee, Mei-Ling Ting (International Journal of Statistics in Medical Research, 2014)
On the basis of longitudinal Kellgren-Lawrence (KL) grades of knee radiographs obtained from the Multicenter Osteoarthritis Study (MOST), we examine the association of obesity and race with severity of knee osteoarthritis (OA). We use the proportional odds model with mixed effects to conduct the analysis. Repeated KL grades were modeled as ordinal longitudinal measures, and a random effect term was included to adjust for the within-subject correlation among the KL grades over time. We found that African Americans and more obese participants in MOST have a greater risk of developing severe knee OA.